PENERAPAN MODEL DRILLS BERBASIS ICT (INFORMATION AND COMUNICATION TECHNOLOGY) UNTUK MENINGKATKAN HASIL BELAJAR IPS: Penelitian Tindakan Kelas Pada Siswa Kelas VIII A SMP Diponegoro 1 Rawamangun Jakarta Timur - Qolbiyah, Shifa; Siswono, Eko; Kurniawan, Nandi (Program Studi Pendidikan IPS Universitas Negeri Jakarta, 2020)
This research aims to find out the implementation of ICT based Drills model to improve student learning result of social sciences subject. This research has been done in class VIII A with 32 students in Diponegoro I Junior High School East Jakarta school year of 20182019 from March to May 2019. The method used in this research is classroom action research that has 3 cycles where each cycle consists of four steps: Planning, Acting, Observing, and Reflecting. According to the research finding, the learning result occurs enhancement in each cycle. In the cycle 1 as big as 21,8% (7 students) reaches score that is above the minimum completeness criteria 75 with the average of learning result 54,56, in cycle 2 becomes 50% (16 students) reaches score that above the minimum completeness criteria 75 with the average of learning result 76,75, and in cycle 3 becomes 93,75% (30 students) reaches score that is above the minimum completeness criteria 75 with the average of learning result 85,12.